اختيارات الإمام عبد الرحمان الثعالبي في تفسيره الجواهر الحسان في تفسير القرآن - جمعا ودراسة - علي بالمصطفى; الأزهر الأقريد; حمزة مسعودي (University of Eloued-جامعة الوادي, 2022)
"موضوع البحث الموسوم بـ: "" اختيارات الإمام عبد الرحمان الثعالبي في تفسيره الجواهر الحسان في تفسير القرآن- جمعا ودراسة"" وإشكاله الرئيسي الذي حاولنا الإجابة عنه: ما هي أهم اختيارات الإمام الثعالبي في الأقوال التفسيريّة؟ وفيما تتمثل وجوه وقواعد الترجيح وتعاليل الترجيح في اختياراته التفسيريّة من خلال سورة البقرة؟, و للإجابة على هذه الإشكاليّة, جاء البحث مقسما إلى مبحثين: خصص الأول في التعريف بحدود البحث، والثاني لبيان اختيارات الثعالبي في سورة البقرة، ومن أهم النتائج التي توصلنا إليها: -الإمام الثعالبي عاش في عصر عرف واقعا سياسيا متأزما، ورغم ذلك فإنه تمكن من الإشتغال بالعلوم و تحصيلها، و إفادة الناس بها، فلا يقبل ممن يتعذر بالظروف على طلب العلم. -الإمام الثعالبي إمام علم في علوم التفسير و غير ذلك من العلوم، فهو موسوعة تفنن في علوم شتىّ. -الإمام الثعالبي كان يتحرى الدقة في النقل على العلماء. - تناولت اختيارات الثعالبي في التفسير موضوعات متعددة، منها ماله صلة بالعقيدة، وعلوم القرآن، و التفسير، و اللغة، وغير ذلك . "The topic of the research tagged with: “Imam Abd al-Rahman al-Thaalbi’s choices in his interpretation of the jewels al-Hasan in the interpretation of the Qur’an - collection and study” and its main problem that we tried to answer: What are the most important choices of Imam al-Thaalbi in exegetical sayings? And what are the aspects and rules of weighting and the explanations of weighting in his explanatory choices through Surat Al-Baqarah? And to answer this problem, the research was divided into two sections: The first was devoted to defining the limits of the research, and the second to explain the choices of Al-Thaalibi in Surat Al-Baqarah, and among the most important results we reached: -Imam al-Thaalibi lived in an era that knew a tense political reality, and despite that, he was able to engage in and acquire sciences, and to benefit people with them, so he does not accept those who are unable to seek knowledge under circumstances. Al-Imam Al-Thaalibi is an imam of science in the sciences of interpretation and other sciences, as he is an encyclopedia of art in various sciences. -Imam al-Thaalibi was investigating the accuracy of transmission on scholars. Al-Thaalibi's choices in interpretation dealt with various topics, including his money related to faith, the sciences of the Qur'an, interpretation, language, and so on..
مذكرة ماستر
Keywords: عبد الرحمان الثعالبي /الجواهر الحسان/تفسير القرآن; Abd al-Rahman al-Thalabi / Al-Jawahir Al-Hassan / Interpretation of the Qur’an